Faktor-Faktor yang Berhubungan dengan Kejadian ISPA pada Anak Balita di Posyandu Melati, Kelurahan Cibinong - Dian Fajariati Kartini; Andriati Reny Harwati (Jurnal Persada Husada Indonesia, 2019)
Acute Respiratory Infection is a health problem that causes high mortality in infants and toddlers, which is about 1 in 4 deaths that occur. Acute Respiratory Infection is very vulnerable to attack in infants and toddlers because the immune system is easily decreased and is still very low compared to adults. The purpose of this study was to determine the determinants of Acute Respiratory Infection in under five years old children in Posyandu Melati Cibinong Village in 2019. This study used a correlation study. The sample in this study were mothers who had children aged 1-5 years and lived in the Posyandu Melati area of ​​Cibinong Village, as many as 99 respondents. Chi square analysis test results concluded that there was a significant relationship between the history of exclusive breastfeeding with the incidence of Acute Respiratory Infection in infants with p-value = 0,000, and there was a significant relationship between smoking behavior of family members with the incidence of Acute Respiratory Infection with p-value = 0.006. Meanwhile, the results of the study showed that there was no significant relationship between nutritional status and the incidence of Acute Respiratory Infection in children under five years (p-value = 0.248). The recommendations of this study are: that mothers should give exclusive breastfeeding to their toddlers, and to family members not to smoke in the house or near toddlers.